The enchantress of Florence : a novel - Rushdie, Salman (London : Jonathan Cape, 2008)
A tall, yellow-haired young European traveller calling himself 'Mogor dell'Amore', the Mughal of Love, arrives at the court of the real Grand Mughal, the Emperor Akbar, with a tale to tell that begins to obsess the whole imperial capital.
Includes bibliographical references (pages 350-355).
Keywords: Women -- Mogul Empire -- Fiction; Historical fiction